Epidemiology of Adults and Children Treated for Nontuberculous Mycobacterial Pulmonary Disease in Japan - Izumi, Kiyohiko; Morimoto, Kozo; Hasegawa, Naoki; Uchimura, Kazuhiro; Kawatsu, Lisa; Ato, Manabu; Mitarai, Satoshi (Annals of the American Thoracic Society, 2019)
The epidemiology of nontuberculous mycobacterial pulmonary disease (NTM-PD) remains unclear in the majority of countries, including Japan. To estimate the nationwide incidence and prevalence of NTM-PD in Japan and to describe case characteristics and geographical variation. In this cross-sectional study, we analyzed data from all health insurance claims made for NTM-PD collected from the National Database in Japan between 2009 and 2014. A patient with NTM-PD was identified on the basis of at least one claim submitted with International Classification of Diseases Version 10 codes associated with NTM-PD and at least one claim for combinations of antimycobacterial medications. We calculated the incidence and prevalence rates for 2011 by sex, age group, and geographical region and evaluated comorbidities. The numbers of incident and prevalent NTM-PD cases in 2011 were 11,034 (8.6 per 100,000 person-years; 95% confidence interval [CI], 8.5-8.8) and 37,063 (29.0 per 100,000 persons; 95% CI, 28.7-29.3), respectively. Among incident cases, the mean ± standard deviation age was 69.3 ± 12.3 years, and 69.6% were women. The incidence rate sharply increased after 50 years of age in both sexes and was higher among women in all age groups, except for those aged 80 years and above. Among men, the incidence rate was highest among older adults, with a sharp increase in comorbidities with age. The most prevalent comorbidities were bronchiectasis for women and chronic obstructive pulmonary disease for men. Most southwestern regions showed high incidence rates, except for Okinawa, which is the southernmost island in Japan. Our results revealed that the incidence and prevalence rates of NTM-PD were among the highest worldwide, despite the conservative treatment-based case definition of NTM-PD used in this study. Prolonged disease duration accompanied by comorbidities probably affected this high prevalence rate. Older adults and women had an especially high risk of NTM-PD, but older men with comorbidities also require more attention. Further studies are required to investigate the factors underlying this geographical variation.